Not just language: an analysis of discursive constructions of disability in sentencing remarks. Issue 3 (4th May 2017) - Sullivan, Frankie
Abstract: It is well established that people with disability (PWD) experience disproportionately high rates of domestic and family violence. Inquiries into this issue have focused on tangible barriers to accessing justice, such as onerous standards of capacity and the lack of communication aids available to those wanting to report crime or give evidence. However, relatively little research has sought to examine the social and cultural factors that compromise the justice outcomes for PWD as victims of crime. By employing the methodology of discourse analysis against a framework of critical disability studies, this research highlights how disability is constructed by judges in the sentencing remarks of those convicted of domestic homicide offences against PWD. The central argument of this article is that there appears to be underlying attitudes towards disability that affect the way family members, intimate partners and carers convicted of violent crimes against PWD are sentenced. These attitudes are reflected in the language used by judges at sentencing, resulting in statements that denigrate disability and even condone such violence. Essentially, this article seeks to demonstrate how an interdisciplinary approach that simultaneously takes into account law, language and power provides a more complete picture of the way PWD who have experienced domestic and family violence are positioned within the criminal justice system.